2020
DOI: 10.2196/18025
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of Technology in Cardiac Rehabilitation and Self-Management: Systematic Qualitative Grounded Theory Review

Abstract: The following pages provide the PRISMA 2009 Checklist for the paper. We note that the PRISMA website 1 states that it was designed with a focus on the reporting of reviews evaluating randomized trials. The website also states that it can be used as a basis for reporting systematic reviews of other types of research, and hence we have used it in this paper. However, the PRISMA focus on reviews of randomized trials means there are important clarification to note in regard to specific questions. Question 2: Part … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…self-set goals) have been recognised as necessary components that can help achieve health outcomes (Lentferink, Oldenhuis, and de Groot 2017). Likewise, literature with a clinical perspective argues that these types of components could also help promote the underlying principle that there must be a shared responsibility between health care providers and patients (Tadas and Coyle 2020;Riegel, Jaarsma, and Lee 2019). In the present study, respondents with clinical expertise often emphasised the important balance between giving the patient the initiative while at the same time not leaving them completely alone in the process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…self-set goals) have been recognised as necessary components that can help achieve health outcomes (Lentferink, Oldenhuis, and de Groot 2017). Likewise, literature with a clinical perspective argues that these types of components could also help promote the underlying principle that there must be a shared responsibility between health care providers and patients (Tadas and Coyle 2020;Riegel, Jaarsma, and Lee 2019). In the present study, respondents with clinical expertise often emphasised the important balance between giving the patient the initiative while at the same time not leaving them completely alone in the process.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, it is plausible that different strategies could also have varying effects on the distinct processes of self-care that are proposed by the Middle-Range Theory of Self-Care of Chronic Illness (e.g. the same factor could act as a facilitator or a barrier, depending on the person, the need, and the context) (Harvey, Dopson, and McManus 2015;Tadas and Coyle 2020). Moreover, research has suggested that persuasive design strategies such as goal-setting, suggestions, or reminders are key components of eHealth interventions that aim to promote healthy lifestyles (Lentferink, Oldenhuis, and de Groot 2017).…”
Section: Designing Ehealth For Self-care With Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic reviews have highlighted the potential of digital health interventions to support rehabilitation and subsequent self-management of cardiovascular conditions [ 9 - 11 ]. However, significant shortcomings were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Piette et al [ 10 ] highlighted the need for future interventions to incorporate advances in behavioral theories and artificial intelligence in order to be more effective and adaptive to the changing needs of patients. Despite recent calls for technology that supports personalization and focuses on user needs, Tadas et al [ 11 ] found that, with notable exceptions, prior research in the cardiovascular domain has made limited use of user-centered approaches. This is consistent with the findings of Siegers et al [ 12 ], who also reported that most developers of digital interventions for cardiac self-management did not engage with the direct experiences of patients, such as those who have attended rehabilitation programs.…”
Section: Introductionmentioning
confidence: 99%